Pengaruh ULLTT terhadap Penurunan Nyeri terhadap Kasus HNP Cervical - Lilik Sigit Wibisono; Syurrahmi Syurrahmi; Widya Ervianta; Ni Kadek Krisna Dwi Patrisia; Lulu'ah Feby Purwanti (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: Hernia Nucleus Pulposus (HNP) is a condition when the pad or disc (soft gel disc or nucleus pulposus) between the vertebrae (spine) comes out of its original position or is torn and pinches the nerve behind it. Many people know it as